President Prabowo Subianto's Speech at the 97th Youth Pledge Commemoration: Critical Discourse Analysis Using Norman Fairclough's Model - Haryo Untoro (Journal of Language, Literature and Teaching, 2026)
This study aims to examine the construction and influence of President Prabowo Subianto's discourse in his speech commemorating the 97th Youth Pledge, which was published on October 28, 2025, on the Sekretariat Presiden ‘Presidential Secretariat’ YouTube channel. The theory used is Norman Fairclough's critical discourse analysis model, focusing on three dimensions of discourse, namely the textual dimension, the discourse practice dimension, and the social practice dimension. This study is descriptive and qualitative, consisting of three stages, namely data collection, data analysis, and data presentation along with the analysis results. The main data for this study was President Prabowo Subianto's speech commemorating the 97th Youth Pledge, which was listened to and transcribed from the Presidential Secretariat's YouTube channel. Supporting data included screenshots from the official YouTube channel of the Sekretariat Presiden ‘Presidential Secretariat’ and the YouTube channels of non government media outlets, namely Kompas TV and Metro TV, as well as several related references. The results show that this speech was composed in the spirit of inclusivity, to raise awareness and unity among various groups, and to call on young people to contribute to the advancement of Indonesia. The emphasis on the importance of the role of youth for the glory of the nation is a discourse based on nationalism. This ideology was then presented and distributed in order to shape public perception of the ideal Indonesian youth.